Evaluasi Tingkat Bahaya Longsor Terhadap Lahan Permukiman Di Gunung Padang Kota Padang Sumatera Barat - elfia, Sisri; Juita, Erna; Zahara, Leni (STKIP PGRI Sumbar, 2013)
The research was conducted in order to: 1) determine the physical properties of soil on the hills of Mount Padang. 2) determine the level of avalanche danger on every unit of land in the area of Mount Padang Padang West Sumatra. Samples taken there are 3 villages namely, Kel. Aie Mato, kel. Seberang Palinggam, and Kel. Bukit Gado-Gado hill. With sampling technique was purposive sampling. The results showed that (1) the physical properties of soil (texture, structure, pH, drainage, consistency). Dusty loam texture and dusty clay loam, with a plate of soil structure, blocky and poles, as well as the pH level indicates the acidity of the soil is neutral and acidic class. On soil drainage class is somewhat good because they have good air circulation, and a crumbly consistency and somewhat firm, which has a crumbly consistency good condition and easily processed, while the firm rather poor soil conditions and difficult to process. At the village level 3 slope slope between 15-25% - 25-40%. (2) the level of avalanche danger on land settlement seen from the physical properties of soil, slope, it can know the Ex area. Aie Mato and Kel. Bukit Gado-Gado hill with a moderate level of avalanche danger, and in Ex. Seberang Palinggam with high levels of avalanche danger